Twin Reversed Arterial Perfusion Sequence Diagnosed Late in the Third Trimester: A Case Report and Literature Review - Tafese Dejene; Abdi Kebede; Getahun Fetensa; Delayehu Bekele; Telila Mesfin; Kelil Hussen (Clinical Case Reports)
ABSTRACT The twin reversed arterial perfusion (TRAP) sequence is a rare complication associated with monochorionic twins. It is characterized by blood flow from the umbilical artery of the normal (pump) twin to the umbilical artery of the abnormal (acardiac) twin via artery‐to‐artery anastomosis. This condition is associated with 100% mortality in the acardiac twin and a high rate of perinatal morbidity and mortality in the pump twin, primarily due to intrauterine hypoxic injury, heart failure, and prematurity. Following delivery, the surviving pump twin may experience adverse neurodevelopmental outcomes and heart failure, necessitating ongoing follow‐up care. The goal of managing pregnancies complicated by the TRAP sequence is to deliver a healthy, near‐term pump twin through early detection, timely intervention, and continuous follow‐up. However, in low‐resource settings, such as the case presented here, the condition may progress undiagnosed into the third trimester due to a lack of experienced physicians and/or obstetric ultrasound scans. This case report serves as an entry point for a comprehensive review of the literature on management options for the TRAP sequence, specifically focusing on factors to consider when managing patients conservatively in resource‐limited environments or in cases that are referred or diagnosed late.